Relayout dan Pengurangan Jumlah Operator Line Produksi XS 156 - Louis Jonathan (Jurnal Titra, 2019)
PT. Schneider Electric Manufacturing Batam is one company that manufactures electronic equipment. Over time, there is an increase in customer demand every year. The problem that occurs is that the XS 156 production line is unable to meet customer demand. This happens because there is a bottleneck on the XS 156 production line. The location of the bottleneck is located in Resin Cells. Therefore, PT. Schneider Electric Manufacturing Batam plans to add one new resin machine. The obstacle that determines the unavailability of land used to lay new resin machines is that the land available on the XS 156 production floor is limited. PT. Schneider Electric Manufacturing Batam relates to the XS 156 production line to obtain land that can be used to install new resin machines. Congestion. PT. Schneider Electric Manufacturing Batam evaluates the number of operators found in the XS 156 production line. The results of the evaluation show that there are 5 operators over the XS 156 production line. There has been a change in the bottleneck on the production floor of XS 156. Resin. After replacing the engine, the jam switches to the Laser cell. The savings obtained from this project are USD 46,696.96.